The effects of genistein and daidzein on cell proliferation kinetics in HT29 colon cancer cells: the expression of CTNNBIP1 (beta-catenin), APC (adenomatous polyposis coli) and BIRC5 (survivin) - Lepri, Sandra Regina; Zanelatto, Leonardo Campos; Goncalves da Silva, Patricia Benites; Sartori, Daniele; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Springer, 2014)
Soybean isoflavonoids have received significant attention due to their potential anticarcinogenic and antiproliferative effects and possible role in many signal transduction pathways. However, their mechanisms of action and their molecular targets remain to be further elucidated. In this paper, we demonstrated that two soybean isoflavones (genistein and daidzein) reduced the proliferation of the human colon adenocarcinoma grade II cell line (HT-29) at concentrations of 25 and 50-100 mu M, respectively. We then investigated the effects of genistein and daidzein by RT-PCR on molecules that involved in tumor development and progression by their regulation of cell proliferation. At a concentration of 50 mu M genistein, there was suppressed expression of beta-catenin (CTNNBIP1). Neither genistein nor daidzein affected APC (adenomatous polyposis coli) or survivin (BIRC5) expression when cells were treated with concentrations of 10 or 50 mu M. These data suggest that the down-regulation of beta-catenin by genistein may constitute an important determinant of the suppression of HT-29 cell growth and may be exploited for the prevention and treatment of colon cancer.
Keywords: Genistein; Daidzein; Proliferation kinetics; beta-catenin; Surviving; APC; HT29 cell